2020
DOI: 10.3390/ijerph17186849
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sport and Physical Education in Northern Ireland School Children: A Cross-Sectional Study

Abstract: Internationally, insufficient physical activity (PA) is a major health concern. Children in Northern Ireland (NI) are recorded as having the lowest levels of PA in the United Kingdom (UK). To date, validated and representative data on the PA levels of NI school children are limited. The aim of this study was to provide surveillance data on self-reported PA, sport and physical education (PE) participation of school children in NI. Differences between genders and factors associated with PA were also examined. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
17
0
1
Order By: Relevance
“…For this, detailed information on the correlates positively and negatively associated with PA behaviour are essential. Common approaches to PA correlate investigations have compared adolescents who meet daily PA guidelines against those who do not ( Connolly et al, 2020 , Mehtälä et al, 2020 ), yet being physically active on a daily basis is a challenge for adolescents nationally and globally ( Guthold et al, 2020 ), one that is reflected in current WHO PA guidelines ( Bull et al, 2020 ). Therefore, this study provided a more nuanced investigation by fractionating PA behaviour and examining the socio-ecological correlates associated with those who were daily active and adding three other categories with decreasing levels of PA ‘active’, ‘somewhat active’ and ‘inactive’.…”
Section: Discussionmentioning
confidence: 99%
“…For this, detailed information on the correlates positively and negatively associated with PA behaviour are essential. Common approaches to PA correlate investigations have compared adolescents who meet daily PA guidelines against those who do not ( Connolly et al, 2020 , Mehtälä et al, 2020 ), yet being physically active on a daily basis is a challenge for adolescents nationally and globally ( Guthold et al, 2020 ), one that is reflected in current WHO PA guidelines ( Bull et al, 2020 ). Therefore, this study provided a more nuanced investigation by fractionating PA behaviour and examining the socio-ecological correlates associated with those who were daily active and adding three other categories with decreasing levels of PA ‘active’, ‘somewhat active’ and ‘inactive’.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although the decline in PA during school holidays is well established 7,8 , it is not yet known how lockdown will have affected the PA levels of adolescents and in particular adolescent girls. It is recognised that adolescent females typically have lower levels of PA than their male counterparts 9-11 and prior to the pandemic, only 7.2% of adolescent girls in NI were meeting PA guidelines 12 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Although the decline in PA during school holidays is well established 7,8 , it is not yet known how lockdown will have affected the PA levels of adolescents and in particular adolescent girls. It is recognised that adolescent females typically have lower levels of PA than their male counterparts 9-11 and prior to the pandemic, only 7.2% of adolescent girls in NI were meeting PA guidelines 12 .Previous research has shown that school closures and separation from friends can cause stress and anxiety in children and adolescents 13 . Social media and technology can help maintain social contact and during the pandemic increases in recreational screen-based activities, and time spent on social media have been reported 14 .COVID-19 restrictions and the health and wellbeing of adolescent girls 3 However, there is evidence of an association between mobile screen use and adverse mental health and wellbeing outcomes in young people 15,16 .…”
mentioning
confidence: 99%
“…Similarly, in US children, boys and girls with higher household income were 2.0 and 2.6 times more likely to achieve physical activity guidelines during adulthood, respectively [ 42 ]. Children with low socio-economic status generally have low participation in school and community sports activities [ 43 ], though not habitual MVPA as measured by accelerometery. While SES has negligible influence on time spent in MVPA at single points in time in UK studies, including our previous analyses of the Gateshead Millennium Study cohort [ 20 ], SES might influence trajectories via an influence on sustained participation in organised sport and physical activity.…”
Section: Discussionmentioning
confidence: 99%